The Diagnostic Value of Bile Acids and Amino Acids in Differentiating Acute Coronary Syndromes - Yu Q; Zhao F; Wang S; Jia X; Shen S; Zhao X; Li Y; Song J; Sun M; Liu X; Liu Z (International Journal of General Medicine)
Qian Yu,1– 3,* Furong Zhao,3,4,* Shuang Wang,4 Xingwang Jia,1,5 Shuang Shen,2 Xiaofeng Zhao,2 Ying Li,3,4 Jiaolei Song,2 Miao Sun,1,5 Xin Liu,1,2 Zhining Liu1,6 1Post Graduate School of Jinzhou Medical University, Jinzhou, Liaoning, People’s Republic of China; 2Huludao Central Hospital Teaching Base of Jinzhou Medical University, Huludao, Liaoning, People’s Republic of China; 3Liaoning Provincial Key Laboratory of Clinical Oncology Metabolomics, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou, Liaoning, People’s Republic of China; 4Clinical Research department, Dalian Boyuan Medical Technology Co., Ltd, Dalian, Liaoning, People’s Republic of China; 5Department of Laboratory Medicine, General Hospital of Fushun Mining Bureau of Liaoning Health Industry Group, Fushun, Liaoning, People’s Republic of China; 6Ultrasound Department, First Affiliated Hospital of Jinzhou Medical University, Jinzhou, Liaoning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhining Liu, First Affiliated Hospital of Jinzhou Medical University, Jinzhou, Liaoning, 121001, People’s Republic of China, Tel +86 15941695215, Email liuzhiningfuyi@163.com Xin Liu, Huludao Central Hospital Teaching Base of Jinzhou Medical University, Huludao, Liaoning, 125001, People’s Republic of China, Tel +86 15941695215, Email lyy66112@163.comPurpose: Acute coronary syndrome (ACS), comprising unstable angina and acute myocardial infarction, is the most dangerous and fatal form of coronary heart disease. This study evaluates serum bile acids (BAs) and amino acids (AAs) as potential predictors of AMI in UA patients.Patients and Methods: A total of 72 Non-Coronary Artery Disease (NCAD) patients, 157 UA patients, and 79 AMI patients were analyzed. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) measured 15 bile acids and 19 amino acids. The data was split into training and validation sets (7:3). Univariate and multivariate analyses were performed. Diagnostic value and clinical benefits were assessed using receiver operating characteristic (ROC) curves, decision curve analysis, and metrics such as the area under the curve (AUC), integrated discrimination improvement (IDI), and net reclassification improvement (NRI).Results: Orthogonal partial least squares discriminant analysis (OPLS-DA) of serum BAs and AAs effectively differentiated NCAD, UA, and AMI groups. The differences in serum BA and AA profiles between UA and AMI patients were primarily driven by four metabolites: deoxycholic acid (DCA), histidine (His), lysine (Lys), and phenylalanine (Phe). Together, they had an AUC of 0.830 (0.768 in the validation cohort) for predicting AMI in UA patients. After adjusting for multiple confounding factors, DCA, His, Lys, and Phe were independent predictors distinguishing UA from AMI. The results of AUC, IDI, and NRI showed that adding these four biomarkers to a model with clinical variables significantly improved predictive value, which was confirmed in the validation cohort.Conclusion: These findings highlight the association of DCA, His, Lys, and Phe with AMI, suggesting their potential role in AMI pathogenesis.Keywords: bile acid, amino acid, unstable angina, acute myocardial infarction, metabolomics